Correlation between Myopia Progression and Blue Light Exposure in Adolescents - Zohaib, Ahmed; Awan, Ayyaz Hussain; Farooq, Nesr; Manzoor, Asif; Rehman, Aftab ur; Orakzai, Asif Mehmood; khan, Bilal (Journal of Neonatal Surgery, 2025)
Background: To examine the correlation between blue light exposure from digital screens and myopia progression in adolescents over a one-year period. Methods: A prospective observational study was conducted from May 2023 to September 2024, involving 62 adolescents aged 10 to 18 years. Participants underwent baseline and follow-up ophthalmic assessments, including cycloplegic refraction and axial length measurement. Data on screen time, device use, blue light filter usage, and outdoor activity were collected through structured questionnaires. Myopia progression was analyzed in relation to these factors using appropriate statistical methods. Results: Adolescents with more than 4 hours of daily screen time showed significantly greater myopia progression (–0.88 ± 0.30 D/year) compared to those with less than 2 hours (–0.40 ± 0.18 D/year; p = 0.003). Use of blue light filters was associated with slower progression (p = 0.041), and outdoor exposure of at least one hour per day had a protective effect (p = 0.010). Conclusion: Prolonged blue light exposure from digital devices is significantly associated with accelerated myopia progression in adolescents. Promoting screen time limits, blue light protection, and outdoor activity may help reduce this risk.